Pengaruh Pemberian Terapi rTMS dengan Kualitas Tidur Pasien Post Stroke Iskemik - Desfarina, Desfarina (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
ABSTRACT Background: Stroke is the second leading cause of death and disability in the world. One of the complications of stroke is sleep disorders. Apart from medication, repetitive Transcranial Magnetic Stimulation (rTMS) is an alternative therapy for managing sleep disorders. Objective: This study aimed to assess the effect of rTMS therapy on the sleep quality of post ischemic stroke patients at RS Dr. M. Djamil Padang. Method: This analytical observational study utilized a cross sectional design conducted at the Neurological Polyclinic of RS Dr. M. Djamil Padang from August 2023 to February 2024. Samples were taken using consecutive sampling techniques based on inclusion and exclusion criteria. High frequency rTMS stimulation was administered to the left DLPFC (dorsolateral prefrontal cortex) 10 times. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The influence between research variables was tested bivariate using the T test, Mann-Whitney test, Fisher test, and McNemar test. Results: The average PSQI score in patients before rTMS therapy was 9.83±3.996, and after rTMS therapy was 4.13±3.327. Based on the results of bivariate analysis, there is a significant effect between giving rTMS therapy and improving sleep quality in post ischemic stroke patients with a value of p<0.001. Discussion: Post ischemic stroke patients who underwent rTMS therapy experienced a decrease in average PSQI score with a mean difference of 5.70, and most patients had good sleep quality after undergoing rTMS therapy in this study (75%). Giving high frequency rTMS to the left DLPFC enhances cortical and subcortical stimulation, thereby improving sleep quality. Keywords: rTMS, sleep quality, stroke, PSQI.